STEM-08. MODELING AND UNDERSTANDING GLIOBLASTOMA EDGE CELLS. (14th November 2022) - Maturi, Naga Prathyusha; Neves, Ines; Dang, Yonglong; Yildirim, Irem; Latini, Francesco; Bergström, Tobias; Sundström, Anders; Xing, Pengwei; Jarvius, Malin; Larsson, Rolf; Fryknäs, Mårten; Ryttlefors, Mats; et al.
Abstract: Glioblastoma is a devastating disease with an overall median survival of 8 months from diagnosis. The majority of patients die of a tumor relapse in close proximity of the resected primary tumor. Glioblastoma is intensely researched but most studies have been performed on tissues and cultures derived from the bulk tumor while it is the remaining edge cells that cause lethality. Investigations of edge cells are rare and few experimental models exist. Here we have established and analyzed a series of matched cell cultures derived from the tumor bulk and outer edge of six IDH wildtype glioblastoma patients with the purpose to understand glioblastoma edge cell biology. Tumor samples were resected guided by 5-ALA fluorescence using neuro-navigation and stringent procedures to not contaminate edge samples with bulk tumor cells. First bulk tumor samples were resected from 5-ALA fluorescent tissue. After removal of all fluorescent areas and careful irrigation of the cavity the edge sample was resected 1-2 cm outside of the fluorescent border in a non-eloquent area. Following dissociation the samples were used in sphere assays and for explantation. There was a significant difference in self-renewal across all patients between matched bulk and edge cultures, in line with results from sphere assays on acute cells, suggesting maintenance of glioblastoma cell properties in established cultures. Invasion analysis showed a reverse significant difference between matched bulk and edge cultures strengthening a general functional distinction between tumor bulk and edge cells across patients. To investigate the molecular basis of our findings we performed whole exome sequencing (WES) and combined single cell RNA- and ATAC-sequencing (10X Multiome). Analyses are ongoing but WES data does not support genetic causes for their differences while the 10X Multiome data indicate that epigenetic regulation may underlie the different properties of bulk and edge glioblastoma cells.